Binding properties of the complex formed by the Arabidopsis TALE homeodomain proteins STM and BLH3 to DNA containing single and double target sites - Viola, Ivana Lorena (2009)
We have analyzed the DNA-binding properties of the complex formed by the Arabidopsis TALE homeodomain (HD) proteins STM and BLH3 in comparison with those of the individual proteins. In vitro DNA-binding assays indicated that complex formation increases binding affinity for sequences carrying either a single target site or two such sites arranged in tandem. Complex formation is not correlated with the establishment of new detectable contacts as deduced from missing-nucleoside experiments. Increased binding was also observed when using BLH3 with a mutation that renders the HD unable to bind DNA, suggesting that only the STM functional HD is necessary for tight binding by the complex. Yeast one-hybrid assays using single or double target sites showed that the effect of complex formation is more dramatic for the double target site and that under these conditions competition for binding by the individual proteins is reduced. The results indicate that even if complex formation produces an increase in binding to DNA sequences containing either one or two target sites, the relative increase in binding produced after complex formation is dependent on the type of target sequence that is considered. This differential effect of complex formation on binding may have implications in the regulatory properties of these transcription factors within the cell.